Technology enhanced collaborative learning for learning of calculus - Ahmad Tarmizi, Rohani; Mohd Ayub, Ahmad Fauzi; Abu Bakar, Kamariah; Md. Yunus, Aida Suraya (WSEAS Press, 2010)
Conceptually and pedagogically, Computer-Supported Collaborative Learning (CSCL) has provided positive impact on mathematical learning. Much evidence have been documented on roles of CSCL approach in facilitating various types of learning and enabling new kind of learning experiences. In addition CSCL enable integration of technology in learning activities thus allowing for a “smooth learning flow”. Technology or computer-support learning allows more students to be actively thinking about information, making choices, and executing skills than is typical in teacher-centred learning. Moreover, when technology is used as a tool to support students in performing authentic tasks, the students are in the position of defining their goals, making design decisions, and evaluating their progress. The teacher's role changes as well. As students work on their technology-supported products, the teacher moves around the room, looking over shoulders, asking about the reasons for various design choices, and suggesting resources that might be used. This study aimed to investigate the motivational and cognitive factors enhanced with the integration of an interactive software Autograph in comparison to the conventional way for teaching Calculus at the secondary level. The Autograph has 2D and 3D graphing capabilities for topics such as functions, transformations, conic sections, vectors, slopes and derivatives. A quasi-experimental research design was used for this study with three phases implemented: 1) Introductory lesson on use of Autograph, 2) Integrated collaborative learning in using Autograph software, 3) Assessment using motivation questionnaire, achievement test and the Paas Mental Effort Rating Scale. Teaching and learning utilizing the Autograph software was found to be more superior significantly, t (77) = 2.58, p < .05 compared to the conventional learning mode. However, conventional strategy learners incurs low mental effort compared to used of Autograph. These findings also suggested that in utilizing any technological tools, a comprehensive measures addressing issues of instructional efficiency is crucial especially when involving large scale and formal implementation of technology integration in teaching and learning.